Benthic community establishment on different concrete mixtures introduced to a German deep-water port - Lydia R. Becker (Helgoland Marine Research, 2021)
Abstract Concrete is a widely used building material in coastal constructions worldwide. However, limited natural resources used in the production process, as well as high CO2-emission due to the calcination process of limestone and the thermal energy demand for Portland cement clinker production, raise the demand for alternative constituents. Alternative mixture types should be environmentally friendly and, at best, mimic natural hard substrates. Here five different concrete mixtures, containing different cements (Portland cement and blast furnace cements) and aggregates (sand, gravel, iron ore and metallurgical slags) were made. Three replicate cubes (15 × 15 × 15 cm) of each type were then deployed in a German deep-water Port, the JadeWeserPort, to study benthic community establishment after one year. Results are compared to a similar experiment conducted in a natural hard ground environment (Helgoland Island, Germany). Results indicate marked differences in settled communities in the Port site compared to natural environments. At the Port site community composition did not differ with the concrete mixtures. Surface orientation of the cubes (front/top/back) revealed significant differences in species abundances and compositions. Cubes hold more neobiota in the Port site than in natural hard ground environments. Implications for the usage of new concrete mixtures are discussed.